"They're changing the network just by being there": Reconsidering infrastructures through the frame of disability studies - Raquel Velho (Disability Studies Quarterly, 2021)
Through the case study of wheelchair user accessibility in public transportation in London, United Kingdom, this article aims to show how the field of disability studies can enrich other disciplines––in this particular case, the field of Science and Technology Studies (STS). Firstly, this paper describes the manners in which wheelchair users struggle with various access barriers in transport, from broken technologies to tense social interactions. This is partnered with a discussion on the nature of infrastructures as highly paradoxical things that struggle with temporality and scale. Secondly, this article describes the inclusion mechanisms developed by wheelchair-using passengers to combat this neoliberal-able infrastructure, showing how they are extremely active users of this network. This is used to illustrate how disability studies throws into question long-standing definitions in the field of STS, namely that of infrastructures being "invisible". This article argues that "invisibility" is a category of privilege for infrastructures, and shows how other disciplines can be enriched through dialogue with the field of disability studies.
Keywords: infrastructures; neoliberal-ableism; science and technology studies; built environment; transportation